DigitalWIV-S: Enhancing Students’ Inquiry Skills and Digital Literacy in PCR and Electrophoresis for Sustainable Education - Zulfiani, Zulfiani; Suwarna, Iwan Permana; Fadlilah, Dina Rahma; Sari , Indah Juwita; El Islami, R. Ahmad Zaky; Mnguni, Lindelani (Universitas Negeri Semarang, 2025)
Digital-based learning can mediate technical barriers and create a support system that enhances the effectiveness of education. This study aims to develop biology learning media, DigitalWIV-S, to enhance the inquiry skills and digital literacy of prospective science teachers. The development method follows Hannafin & Peck's model, which includes the phases of Needs Assessment, Design, Development, Implementation, and Evaluation. The research findings indicate that DigitalWIV-S, as a biology learning media, is deemed appropriate and received positive feedback from students. The evaluation of digital literacy is excellent across cognitive, affective, and conative aspects. Students' inquiry skills are very good in problem orientation and data collection; however, abilities in problem formulation, hypothesis structuring, data analysis, and summarizing are categorized as moderate among the students. The developed media for the PCR and Electrophoresis concepts help students understand these topics better, thereby enhancing their inquiry skills and digital literacy. Additionally, the media addresses the limitations of equipment and materials in modern biotechnology practicums.